Wideband Wave-Propagating Components for Wireless RF Communications (IntechOpen, 2025)
This book provides detailed design studies on various microwave and millimeter-wave components, such as modern antennas, well-developed sensors, low-loss waveguides, and high-precision radar structures for wireless RF communications. Innovative methodologies and design approaches to overcoming challenges and enhancing the efficiency of current wireless communication devices have been thoroughly demonstrated, along with experimental validations. The strength of this book lies in its extensive collection of review studies on numerous works available in the literature. Their disadvantages and advantages have been explicitly summarized to provide a comprehensive insight for readers. Then, the feasible techniques proposed in this book offer proper solutions to resolve the disadvantages of prior arts, causing the improvement of the quality of telecommunication networks. These contributions in antennas and wave propagation, sensors, waveguides, and radar systems can be useful for researchers in these fields from both academic and industrial sectors interested in establishing further developments of wireless RF communication systems. This book includes ten chapters discussing several wireless communication applications, which were prepared by various worldwide research groups with extensive track records in RF, microwave and millimeter-wave technologies.